EFEITOS CRÔNICOS DO CLORETO DE MERCÚRIO SOBRE A PRESSÃO ARTERIAL E A REATIVIDADE VASCULAR DE AORTA DE RATAS - Schereider, Ingridy Reinholz Grafites (2020)
The exposure to toxic metal, such as mercury has been shown to be positively associate with some chronic diseases of the cardiovascular system leading to a significant health risk. However, the effects of metals in female rats is poorly investigate. In th